ANALYSIS OF EMPLOYEE SERVICE QUALITY AT GENTUMA RAYA DISTRICT OFFICE, NORTH GORONTALO REGENCY (Jurnal Ilmu Manajemen dan Bisnis, 2025)
This study aims to (1) analyze the quality of employee services at the Gentuma Raya District Office, North Gorontalo Regency, and (2) identify the obstacles present in the process of improving employee service quality at the Gentuma Raya District Office, North Gorontalo Regency. This study uses a Descriptive Qualitative approach, with data collected through in-depth interviews, observation, and documentation. The informants in this study include the Sub-District Head (Camat), the Deputy Sub-District Head (Sekcam), the section responsible forpublic order and peace, and the Village Apparatus. The results of the study indicate that (1) the quality at the Gentuma Raya Sub-District Office is generally quite good, with prompt service from disciplined employees; however, (2) there are still several obstacles in service quality, including a limited number of employees, shortages of facilities such as the public order office (trantib), and other supporting equipment. In addition, inadequate infrastructure and amenities, such as the availability of clean water, chairs, air conditioning (AC), and a leaking ceiling, also hinder the provision of optimal services.